Norsesquiterpene hydrocarbon, chemical composition and antimicrobial activity of Rhaponticum carthamoides root essential oil - Havlik, Jaroslav; Budesinsky, Milos; Kloucek, Pavel; Kokoska, Ladislav; Valterova, Irena; Vasickova, Sona; Zeleny, Vaclav (Phytochemistry, 2009)
A detailed analysis of Rhaponticum carthamoides (Willd.) Iljin root essential oil was carried out by GC, GC-MS and GC-FTIR techniques. In total, 30 components were identified, accounting for 98.0% of total volatiles. A norsesquiterpene 13-norcypera-1(5),11(12)-diene (22.6%), followed by aplotaxene (21.2%) and cyperene (17.9%), were isolated and their structures confirmed by 1D and 2D-NMR spectra (COSY, ROESY, HSQC, HMBC and INADEQUATE). Selinene type sesquiterpenes and aliphatic hydrocarbons were among minor constituents of the essential oil. The oil exhibited antimicrobial activity against 5 of 9 strains of bacteria and yeast, when tested using broth micro-dilution method. Minimum inhibitory concentrations ranged between 32 and 256 microg/ml.
Keywords: kořeny rostlin; oleje rostlin; chromatografie plynová; Anti-Infective Agents; Molecular Structure; kvasinky; plynová chromatografie s hmotnostně spektrometrickou detekcí; mikrobiální testy citlivosti; Leuzea; Gas Chromatography-Mass Spectrometry; Plant Roots; Bacteria; antiinfekční látky; Yeasts; Chromatography, Gas; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; Microbial Sensitivity Tests; Oils, Volatile; oleje prchavé; spektroskopie infračervená s Fourierovou transformací; Spectroscopy, Fourier Transform Infrared; Plant Oils; molekulární struktura